2010
DOI: 10.1007/s12664-010-0047-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic observations around the gastroesophageal junction in patients with symptomatic gastroesophageal reflux disease in South Asia

Abstract: Substantial proportion of patients with symptoms of GERD has abnormal endoscopic findings around the gastroesophageal junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Some previous Asian studies reported that abnormal GEFV was a risk factor of RE, and associated with RE severity in adults as well as in pediatric patients. [2][3][4]7 Our study also confirmed this finding in Vietnamese population. It is well known that the prevalence of RE in Caucasian population is higher than that in Asian population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some previous Asian studies reported that abnormal GEFV was a risk factor of RE, and associated with RE severity in adults as well as in pediatric patients. [2][3][4]7 Our study also confirmed this finding in Vietnamese population. It is well known that the prevalence of RE in Caucasian population is higher than that in Asian population.…”
Section: Discussionsupporting
confidence: 89%
“…The association between GEFV and gastroesophageal reflux disease (GERD) has been already reported in several previous studies. [2][3][4][5][6][7] However, most of these studies were conducted on patients with reflux esophagitis (RE) [2][3][4][5] and there were very few studies on patients with dyspepsia and non-erosive reflux disease (NERD). 6,7 There have been no studies investigating the distribution of abnormal GEFV among patients with dyspepsia, NERD and different grades of RE in the same set of patients.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review found the prevalence of GORD to be 10 -20 percent in the Western world [2]. Community prevalence of GORD in Sri Lanka is not known but a single study done by Nawarathne et al found it closer to 15% [1]. While clinically troublesome heartburn is seen in about 6 percent of the population [3], chest pain may be the sole presenting complaint of GORD [4,5].…”
Section: Epidemiologymentioning
confidence: 99%
“…As such, endoscopy has excellent specificity for the diagnosis of GORD especially when erosive oesophagitis is seen. In a study done on Sri Lankan patients who had symptoms suggestive of GORD, hiatus hernia (HH), columnar lined oesophagus (CLO) and reflux oesophagitis (RO) were found in 14.3%, 9.5% and 13.3% respectively [1]. Based on current literature the use of routine biopsy of the oesophagus to diagnose GORD cannot be recommended in a patient with heart-burn and a normal endoscopy.…”
Section: Establishing the Diagnosis Of Gordmentioning
confidence: 99%
“…Studies have shown an association between higher Hill grades and the frequency of GERD 8 14 . Higher Hill grades are also associated with lower LES pressure 8 , increased prevalence of hiatal hernia 15 , and are able to predict poor response to proton pump inhibitor treatment 16 . The Hill classification has been proven to be reproducible and provides useful information when evaluating patients with suspected GERD who are undergoing endoscopy 8 .…”
Section: Introductionmentioning
confidence: 99%